Electrical conductivity of the nutrient solution its effect on the yield and nutraceutical quality of bell pepper - Pérez-Vazquez, Ema Luz; Gaucín-Delgado, Jazmín Monserrat; Ramírez-Rodríguez, Silvia Citlaly; Sariñana-Aldaco, María de los Ángeles; Zapata Sifuentes, Gerardo; Zuñiga- Valenzuela, Elizabeth (Revista Mexicana de Ciencias Agrícolas, 2020)
The ionic concentration of the nutrient solution in hydroponic systems influences the yield and quality of the harvested fruits. From this perspective, the objective of this study was to determine the effect of the electrical conductivity (EC) of the nutritive solution (NS) on the yield and content of bioactive compounds in bell pepper fruits. Under a completely randomized experimental design with ten repetitions, pepper plants were irrigated with a NS at different EC (1, 2, 3.2 and 4 dS m-1), yield was determined and biactive compounds were quantified in fruits. The results indicate that an electrical conductivity of 3 or higher improves nutraceutical quality but decreases bell pepper yield. The agronomic management of EC in NS is an alternative to increase the nutraceutical quality and antioxidant capacity of bell pepper fruits developed under hydroponic conditions.
Keywords: Capsicum annuum L; nutraceuticals; soilless crops